Influence of Management of Physical Facilities on Quality of Education in Selected Private Universities in Kenya - Nduta, Beth Githaiga; Itegi, Florence M.; Muchanje, Peter N. (Journal of Education and Practice, 2024)
Purpose: The main purpose of this study was to assess the influence of management of physical facilities on quality of education in selected private universities in Kenya. The study aimed to investigate the deans of schools, heads of department and lecturers' perceptions towards management of physical facilities on quality of education in private universities in Kenya. Methodology: The study used two types of research instruments, namely; lecturers' Questionnaire; and deans of schools and departmental heads' Interview Guide. Data was analyzed used mixed methods, involving qualitative and quantitative techniques. Findings: The study revealed that most of the respondents disagreed that there were adequate physical facilities which affected the quality of education in selected private universities in Kenya. Further, there was a significant positive correlation between management of physical facilities and quality of education in private universities. Unique contribution to theory policy and practice: The study recommends that the managers of private universities should ensure allocation of more funds for construction and maintenance of physical facilities for realization of quality education.